An Exploratory Study of Marketing Factors Influencing Fairtrade Food Buying Behaviour in the UK - Yamoah, Fred Amofa (International Review of Management and Marketing, 2013)
The phenomenal growth of the fairtrade industry has attracted increased research interest but little is known as to what marketing factors drive fairtrade retail sales. This gap has profound implications for fairtrade marketing research and the future of the fairtrade industry. To provide a more robust and objective insight this paper draws on the analysis of supermarket loyalty card dataset of 1.7 million fairtrade shoppers to establish the influence of price, promotion and distribution on fairtrade retail sales. Insights from the results show the lack of cross shopping pattern among fairtrade food product shoppers. The results also indicate that the increasing fairtrade retail sales growth is not shopper demand driven but predominately attributable to widened distribution and price increases. The findings of the study offer insights to fairtrade marketing researchers and strategic direction for managers working to ensure that fairtrade thrives as an ethical consumer driven industry. Keywords: Marketing factors; buying behaviour; cross-shopping; loyalty card data; fairtrade. JEL Classifications: M31